How to create a sustainable food industry a practical guide to perfect food - Barrett, Melissa; Brkic, Francesca; Pratesi, Carlo Alberto; Marino, Massimo (Environmental engineer) (New York, NY Routledge, 2024)
"This book presents a practical guide to help businesses navigate the complex topics of sustainability in the food industry. The book takes you on a journey along the food value chain, from farm to fork, exploring key opportunities to increase positive impacts and circularity at each step of the journey. Written by a team of authors with decades of experience in the food industry and academia, it provides guidance on how to analyse sustainability across the value chain and lifecycle of a food product and how to design, implement and communicate strategies to customers. Furthermore, the book shows that there are not always straightforward solutions, but rather choices and trade-offs that require an understanding what is best suited to the product, customers and business in question. It demystifies a variety of topics, such as local sourcing, regenerative agriculture, plant-based protein and the environmental impact of meat production, and draws on a wide-range of case studies from across the globe, to provide concrete, real-world examples. While a perfect food system may not exist, informed decisions can go a long way to reshape and transform the food industry as we know it. This book will be of great interest to professionals working in the food and agriculture industries, as well as students and scholars of sustainable food systems and sustainable business"--
Includes bibliographical references and index.
Keywords: Food industry and trade; Food security; Sustainable agriculture